Pain-related somatosensory evoked potentials in cortical reflex myoclonus. Issue 1 (January 1990) - Kakigi, R; Shibasaki, H; Neshige, R; Ikeda, A; Mamiya, K; Kuroda, Y
Abstract : To elucidate the sensitivity to pain stimuli in patients with cortical reflex myoclonus, pain-related somatosensory evoked potentials (pain SEPs) following CO2 laser stimulation and conventional electrically-stimulated SEPs (electric SEPs) were compared in four patients with cortical reflex myoclonus. The P25 peak of electric SEPs was considerably enhanced but the P320 potential of pain SEPs was of normal amplitude in all patients. After medication, myoclonus was reduced and the amplitude of P25 was decreased, but P320 showed no change. In our previous study of the scalp distribution in normal subjects, a subcortical site, probably the thalamus, was considered to be the generator source of P320. Because most pain stimuli do not reach the cortex, patients with cortical reflex myoclonus are not sensitive to pain stimuli and P320 in pain SEPs is not enhanced.